The modified reliability-based iterative majority-logic decoding algorithm with non-uniform quantization - Haiqiang Chen; Lingshan Luo; Youming Sun; Tuanfa Qin; Yunyi Liu (2013 8th International Conference on Communications and Networking in China : (CHINACOM 2013) : Guilin, China, 14-16 2013, 2013)
This paper investigates the performances of the modified reliability-based iterative majority-logic decoding (MRBI-MLGD) algorithm under different quantization schemes. An efficient non-uniform quantization method is presented for the MRBI-MLGD algorithm. With the non-uniform strategy, the real received symbols will be quantized into integer values before passing to the decoder. The quantized reliability measures exhibit a non-uniform distribution with respect to their original received signals. Furthermore, the quantization resolution can be modified as required. Simulation results show that, when combined with factor correction techniques and a proper quantization parameter r, the MRBI-MLGD with nonuniform quantization performs well with very small quantized bits (3-4 bits) and has very fast decoding convergence speed.